Photovoltaic Hybrid Systems for remote villages - (:unkn) unknown (My University, 2019)
Electricity access in remote areas of Sub-Saharan Africa is limited due to high costs of grid extension to areas characterised by low population and low energy densities. Photovoltaic hybrid systems can be computed using an energy balance equation involving one unknown. For hypothetical village with an average daily energy demand of 153.6 kWh/d, the monthly energy output of photovoltaic modules at Garoua, Cameroon, enabled the evaluation of feasible photovoltaic hybrid (PVHS) options. An option with a renewable energy fraction of 0.557 having lower initial investments is suggested for electrification of more remote villages in Sub-Saharan African countries which have high solar radiation levels. This option comprises a 23.56 kWp PV array, a 15 kWp PV inverter, a 25 kW bi-directional inverter, a battery bank of capacity 324.48 kWh and a 25 kW diesel generator with an operating time of 1309 h/yr or 3.59h/d. The size of the PV array determined is smaller compared to the sizes of PV arrays which have been evaluated in the range 30-45 kWp using HOMER software for medium villages in Senegal.
Keywords: African Research